Modern weapons and military equipment for the issue 2-2025 - Vučković, Dragan M. (Vojnotehnički glasnik / Military Technical Courier, 2025)
China deploys new KJ-3000 early warning aircraft to neutralize the stealth capacities of US stealth fighters; This Is Our Best Look Yet At The Shadowy Hellfire Missile With Pop-Out Sword Blades; Breaking News: Russia Forms First Regiment Equipped with New S-500 Prometheus Air Defense Missile System; Türkiye’s new Altay tank